Probiotic cereal-based fermented functional foods - Arslan, Sultan; Erbas, Mustafa (CRC Press, 2016)
[Abstract Not Available]
Keywords: Biochemistry; Chemistry; Genetic engineering; Probiotics; Biotechnology